1995
DOI: 10.1063/1.113217
|View full text |Cite
|
Sign up to set email alerts
|

Annealing study of electron irradiation-induced defects in SiGe alloys

Abstract: Isochronal annealing experiments on defects produced by 1.5 MeV electron irradiation at room temperature have been performed on n-type SiGe alloys. Two defects have been studied, labeled P1 and P2, with associated energy levels located at EC−0.32 eV and EC−0.49 eV, respectively, and capture cross sections equal to 1×10−15 cm2 and 2×10−15 cm2. P1 anneals out at 560 K and P2 at 470 K. A comparison with the defects known in Si and Ge allows us to propose the following identification: P1 is associated with the 0/−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This subject has already led to the collection of a fair amount of data for other point defects. [7][8][9][10][11][12] Our main motivation in the present study is to determine the energy level positions of both Fe i and Fe i -B s , as a function of the band gap variation due to a change in the Ge content. Then the impact of alloy disorder on the diffusivity is examined, as the disorder is expected to primarily affect the channels through which free iron is supposed to migrate.…”
Section: Introductionmentioning
confidence: 99%
“…This subject has already led to the collection of a fair amount of data for other point defects. [7][8][9][10][11][12] Our main motivation in the present study is to determine the energy level positions of both Fe i and Fe i -B s , as a function of the band gap variation due to a change in the Ge content. Then the impact of alloy disorder on the diffusivity is examined, as the disorder is expected to primarily affect the channels through which free iron is supposed to migrate.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that, unlike other studies in which the as-grown samples experienced proton irradiation [12][13][14][15] or ion implantation 20,21 in order to intentionally induce defects, the samples studied here were found to naturally form from point defects whose possible origin is similar to that seen in previous studies. [12][13][14][15]20,21 It was also found that two divacancy-related defects can be formed, regardless of which dopants were used. 9 In general, the mechanism for an E-center creation is explained by the fact that doping with P results in a contraction of the silicon lattice 24 due to the different atomic radii of P in a Si matrix.…”
Section: A Peak Identification and Suggested Mechanism Of Defect Formentioning
confidence: 50%
“…The dominant defects in the LT-MBE-grown samples are expected to be of intrinsic and/or dopant-related origin, because ͑1͒ the impurity concentration in the MBE-grown layers is low and ͑2͒ the defects found were annealed out without generating any other defects of comparable density. From the authors' previous study of LT-MBE-grown Si, 9 which compared results with defects in Si grown by chemical vapor deposition, 12,13 Czochralski, 12 MBE, 14 -19 and ion implantation, 20,21 the possible origin of the dominant defect, E1 and E11, was suggested as an E center (V -P) plus a singly negatively charged divacancy, V -V (0/Ϫ), complex. It is well known that the V -V (0/Ϫ) is located at E C Ϫ0.42 eV in Si 22,23 and strongly overlaps with the E center.…”
Section: A Peak Identification and Suggested Mechanism Of Defect Formentioning
confidence: 99%
“…So far, many defect research groups have studied defects in silicon grown by chemical vapor deposition ͑CVD͒, 11,12 Czochralski ͑CZ͒ technique, 11 molecular-beam epitaxy, [13][14][15][16][17][18] or ion implantation. 19,20 But there remains some confusion in the literature about the role of dopants as a vacancy complex.…”
Section: Discussionmentioning
confidence: 99%